Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Fine‐scale spatial variation in fitness is comparable to disturbance‐induced fluctuations in a fire‐adapted species - Shaun R. Coutts; Pedro F. Quintana‐Ascencio; Eric S. Menges; Roberto Salguero‐Gómez; Dylan Z. Childs (Ecology, 2021)
The spatial scale at which demographic performance (e.g., net reproductive output) varies can profoundly influence landscape‐level population growth and persistence, and many demographically pertinent processes such as species interactions and resource acquisition vary at fine scales. We compared the magnitude of demographic variation associated with fine‐scale heterogeneity ( 1 ha) fluctuations associated with fire disturbance. We used a spatially explicit model within an IPM modeling framework to evaluate the demographic importance of fine‐scale variation. We used a measure of expected lifetime fruit production, E F , that is assumed to be proportional to lifetime fitness. Demographic differences and their effects on E F were assessed in a population of the herbaceous perennial Hypericum cumulicola (~2,600 individuals), within a patch of Florida rosemary scrub (400 × 80 m). We compared demographic variation over fine spatial scales to demographic variation between years across 6 yr after a fire. Values of E F changed by orders of magnitude over E F as demographic changes caused by time‐since‐fire, a key driver in this system. Our findings show that environmental changes over a few tens of meters can have ecologically meaningful implications for population growth and extinction.

Do plant–microbe interactions support the Stress Gradient Hypothesis? - Aaron S. David; Khum B. Thapa‐Magar; Eric S. Menges; Christopher A. Searcy; Michelle E. Afkhami (Ecology, 2020)
The Stress Gradient Hypothesis (SGH), which predicts increasing ratios of facilitative:competitive interactions with increasing stress, has long been a guiding framework for conceptualizing plant–plant interactions. Recently, there has been a growing recognition of the roles of microbes in mitigating or exacerbating environmental stress for their plant hosts. As such, we might predict, based on the SGH, that beneficial microbial effects on plant performance should be positively associated with stress. Specifically, we hypothesized that support for the SGH would depend on the host plant's habitat specialization such that species that specialize in high stress habitats and thus likely coevolved with the resident microbes would exhibit stronger support for the SGH than non‐specialist plant species. We further hypothesized that support for the SGH would vary with germination frequency, since boosting germination of low‐frequency germinators is one effective means by which microbes can benefit plant species performance. Here, we explore whether plant–microbial interactions support the SGH using 12 plant species native to the Florida rosemary scrub. We conducted factorial experiments that manipulated the presence of microbes in nine soils collected along an elevational stress gradient, and recorded germination frequency and biomass. Microbes increased the germination frequency of four species, all of which had relatively low germination rates. Furthermore, we found support for the SGH in nearly one‐half of the species examined, with soil microbes facilitating germination with increasing stress for 5 of the 12 species tested, and none of the species exhibiting the opposite trend. Support for the SGH was not predicted by either the plant hosts' habitat specialization or germination frequency. In contrast to germination, biomass results showed little support for the SGH, with four of 12 species refuting and one species supporting SGH predictions. Taken together, our study documents that interactions between the soil microbial community and plant species along a stress gradient can support the SGH, but emphasizes that these effects are life‐history‐stage dependent. This work also identifies a common mechanism (germination facilitation) by which microbes can benefit plant species in stressful habitats.

Drivers of vegetative dormancy across herbaceous perennial plant species - Richard P. Shefferson; Tiiu Kull; Michael J. Hutchings; Marc‐André Selosse; Hans Jacquemyn; Kimberly M. Kellett; Eric S. Menges; Richard B. Primack; Juha Tuomi; Kirsi Alahuhta; Sonja Hurskainen; Helen M. Alexander; et al. (Ecology Letters, 2018)
Vegetative dormancy, that is the temporary absence of aboveground growth for ≥ 1 year, is paradoxical, because plants cannot photosynthesise or flower during dormant periods. We test ecological and evolutionary hypotheses for its widespread persistence. We show that dormancy has evolved numerous times. Most species displaying dormancy exhibit life‐history costs of sprouting, and of dormancy. Short‐lived and mycoheterotrophic species have higher proportions of dormant plants than long‐lived species and species with other nutritional modes. Foliage loss is associated with higher future dormancy levels, suggesting that carbon limitation promotes dormancy. Maximum dormancy duration is shorter under higher precipitation and at higher latitudes, the latter suggesting an important role for competition or herbivory. Study length affects estimates of some demographic parameters. Our results identify life historical and environmental drivers of dormancy. We also highlight the evolutionary importance of the little understood costs of sprouting and growth, latitudinal stress gradients and mixed nutritional modes.

Analysis of mating system and genetic structure in the endangered, amphicarpic plant, Lewton’s polygala (Polygala lewtonii) - Joel F. Swift; Stacy A. Smith; Eric S. Menges; Burgund Bassüner; Christine E. Edwards (Conservation Genetics, 2016)

Cross-habitat effects shape the ecosystem consequences of co-invasion by a pelagic and a benthic consumer - David C. Fryxell; Amber R. Diluzio; Maya A. Friedman; Nicklaus A. Menge; Eric P. Palkovacs (Oecologia, 2016)

Interacting environmental mosaics drive geographic variation in mussel performance and predation vulnerability - Kristy J. Kroeker; Eric Sanford; Jeremy M. Rose; Carol A. Blanchette; Francis Chan; Francisco P. Chavez; Brian Gaylord; Brian Helmuth; Tessa M. Hill; Gretchen E. Hofmann; Margaret A. McManus; Bruce A. Menge; et al. (Ecology Letters, 2016)
Although theory suggests geographic variation in species' performance is determined by multiple niche parameters, little consideration has been given to the spatial structure of interacting stressors that may shape local and regional vulnerability to global change. Here, we use spatially explicit mosaics of carbonate chemistry, food availability and temperature spanning 1280 km of coastline to test whether persistent, overlapping environmental mosaics mediate the growth and predation vulnerability of a critical foundation species, the mussel Mytilus californianus . We find growth was highest and predation vulnerability was lowest in dynamic environments with frequent exposure to low pH seawater and consistent food. In contrast, growth was lowest and predation vulnerability highest when exposure to low pH seawater was decoupled from high food availability, or in exceptionally warm locations. These results illustrate how interactions among multiple drivers can cause unexpected, yet persistent geographic mosaics of species performance, interactions and vulnerability to environmental change.

Seasonal wetlands on the Lake Wales Ridge, Florida: does a relict seed bank persist despite long term disturbance? - Cari D. Ficken; Eric Menges (Wetlands Ecology and Management, 2013)

Ability of Matrix Models to Explain the Past and Predict the Future of Plant Populations - ELIZABETH E. CRONE; MARTHA M. ELLIS; WILLIAM F. MORRIS; AMANDA STANLEY; TIMOTHY BELL; PAULETTE BIERZYCHUDEK; JOHAN EHRLÉN; THOMAS N. KAYE; TIFFANY M. KNIGHT; PETER LESICA; GERARD OOSTERMEIJER; PEDRO F. QUINTANA‐ASCENCIO; et al. (Conservation Biology, 2013)
Uncertainty associated with ecological forecasts has long been recognized, but forecast accuracy is rarely quantified. We evaluated how well data on 82 populations of 20 species of plants spanning 3 continents explained and predicted plant population dynamics. We parameterized stage‐based matrix models with demographic data from individually marked plants and determined how well these models forecast population sizes observed at least 5 years into the future. Simple demographic models forecasted population dynamics poorly; only 40% of observed population sizes fell within our forecasts’ 95% confidence limits. However, these models explained population dynamics during the years in which data were collected; observed changes in population size during the data‐collection period were strongly positively correlated with population growth rate. Thus, these models are at least a sound way to quantify population status. Poor forecasts were not associated with the number of individual plants or years of data. We tested whether vital rates were density dependent and found both positive and negative density dependence. However, density dependence was not associated with forecast error. Forecast error was significantly associated with environmental differences between the data collection and forecast periods. To forecast population fates, more detailed models, such as those that project how environments are likely to change and how these changes will affect population dynamics, may be needed. Such detailed models are not always feasible. Thus, it may be wiser to make risk‐averse decisions than to expect precise forecasts from models. Habilidad de los Modelos Matriciales para Explicar el Pasado y Predecir el Futuro de las Poblaciones de Plantas

More than a meal… integrating non‐feeding interactions into food webs - Sonia Kéfi; Eric L. Berlow; Evie A. Wieters; Sergio A. Navarrete; Owen L. Petchey; Spencer A. Wood; Alice Boit; Lucas N. Joppa; Kevin D. Lafferty; Richard J. Williams; Neo D. Martinez; Bruce A. Menge; et al. (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 291–300 Abstract Organisms eating each other are only one of many types of well documented and important interactions among species. Other such types include habitat modification, predator interference and facilitation. However, ecological network research has been typically limited to either pure food webs or to networks of only a few (

Matrix population models from 20 studies of perennial plant populations - Martha M. Ellis; Jennifer L. Williams; Peter Lesica; Timothy J. Bell; Paulette Bierzychudek; Marlin Bowles; Elizabeth E. Crone; Daniel F. Doak; Johan Ehrlén; Albertine Ellis-Adam; Kathryn McEachern; Rengaian Ganesan; et al. (Ecology, 2012)
Demographic transition matrices are among the most commonly applied population models for both basic and applied ecological research. The relatively simple framework of these models and simple, easily interpretable summary statistics they produce have prompted the wide use of these models across an exceptionally broad range of taxa. Here, we provide annual transition matrices and observed stage structures/population sizes for 20 perennial plant species which have been the focal species for long‐term demographic monitoring. These data were assembled as part of the “Testing Matrix Models” working group through the National Center for Ecological Analysis and Synthesis (NCEAS). The data represent 82 populations with >460 total population‐years of observations. It is our hope that making these data available will help promote and improve our ability to monitor and understand plant population dynamics. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

Metacommunity Dynamics Over 16 Years in a Pyrogenic Shrubland - TIMOTHY J. MILLER; PEDRO F. QUINTANA‐ASCENCIO; SATYA MALIAKAL‐WITT; ERIC S. MENGES (Conservation Biology, 2012)
Metacommunity theory allows predictions about the dynamics of potentially interacting species’ assemblages that are linked by dispersal, but strong empirical tests of the theory are rare. We analyzed the metacommunity dynamics of Florida rosemary scrub, a patchily distributed pyrogenic community, to test predictions about turnover rates, community nestedness, and responses to patch size, arrangement, and quality. We collected occurrence data for 45 plant species from 88 rosemary scrub patches in 1989 and 2005 and used growth form, mechanism of regeneration after fire, and degree of habitat specialization to categorize species by life history. We tested whether patch size, fire history, and structural connectivity (a measure of proximity and size of surrounding patches) could be used to predict apparent extinctions and colonizations. In addition, we tested the accuracy of incidence‐function models built with the patch survey data from 1989. After fire local extinction rates were higher for herbs than woody plants, higher for species that regenerated only from seed than species able to resprout, and higher for generalist than specialist species. Fewer rosemary specialists and a higher proportion of habitat generalists were extirpated on recently burned patches than on patches not burned between 1989 and 2005. Nestedness was highest for specialists among all life‐history groups. Estimated model parameters from 1989 predicted the observed (1989–2005) extinction rates and the number of patches with persistent populations of individual species. These results indicate that species with different life‐history strategies within the same metacommunity can have substantially different responses to patch configuration and quality. Real metacommunities may not conform to certain assumptions of simple models, but incidence‐function models that consider only patch size, configuration, and quality can have significant predictive accuracy.

Microhabitat preference constrains invasive spread of non-native natal grass (Melinis repens) - Aaron S. David; Eric S. Menges (Biological Invasions, 2011)

Linking the patterns in soil moisture to leaf water potential, stomatal conductance, growth, and mortality of dominant shrubs in the Florida scrub ecosystem - Sonali Saha; Theresa M. Strazisar; Eric S. Menges; Patrick Ellsworth; Leonel Sternberg (Plant and Soil, 2008)

Genetic change following fire in populations of a seed-banking perennial plant - Rebecca W. Dolan; Pedro F. Quintana-Ascencio; Eric S. Menges (Oecologia, 2008)

Allelopathic effects of Ceratiola ericoides (Empetraceae) on germination and survival of six Florida scrub species - Rebecca E. Hewitt; Eric S. Menges (Plant Ecology, 2008)

DEMOGRAPHY OF THE ENDEMIC MINT DICERANDRA FRUTESCENS IN FLORIDA SCRUB - Eric S. Menges (Ecology, 2008)
Florida scrub supports many endemic species in a pyrogenic shrubland on xeric yellow sands. One genus with multiple endemics is the mint Dicerandra, with its five narrowly endemic species most prevalent in edges and recently burned areas. Study of the demography of Dicerandra frutescens, an endemic and endangered mint restricted to Florida scrub, began in September 1988. Eleven populations have been studied at various locations across Archbold Biological Station and at one privately held site. Some populations, particularly along fire lanes, have been added during the study. Survival and recruitment data were initially collected monthly but were later collected quarterly in September, December, March, and June. Each annual census in September also recorded the life history stage for that “year” (the year including any censuses after the prior September census) and measures of size (basal diameter, number of branch tips, number of reproductive branch tips). Survival variables representing monthly, quarterly, and annual survival were also assembled. These survival variables contain information on the type of plant recruiting (seedling or new adult) or, for plants already in the data set, whether the plant survived the interval, died during the interval, was already (previously) dead, or whether survival could not be ascertained (no tag, no plant). Several populations were subjected to prescribed burns during the study. For years with burns, variables summarize whether plants (or quadrats) were burned or not. This data set consists of 5530 records, each an individual plant, from 1988 through 2004. Published analyses based on data from 1990–2000 found that finite rates of increase were greater than 1 for populations less than six years post‐fire, but thereafter populations were predicted to decline. Similarly, populations in fire lanes were most successful when the time‐since‐disking was short. A yard‐edge population showed variable demography. Stochastic simulations in Florida scrub sites suggested an optimal fire return interval of 6–12 years (regular fires) or 6–21 years (stochastic fires). Data collection on this project is continuing, and we anticipate updating data periodically.

Using Population Viability Analysis to Predict the Effects of Climate Change on the Extinction Risk of an Endangered Limestone Endemic Shrub, Arizona Cliffrose - JOYCE MASCHINSKI; JOANNE E. BAGGS; PEDRO F. QUINTANA‐ASCENCIO; ERIC S. MENGES (Conservation Biology, 2006)
The threat of global warming to rare species is a growing concern, yet few studies have predicted its effects on rare populations. Using demographic data gathered in both drought and nondrought years between 1996–2003 in central Arizona upper Sonoran Desert, we modeled population viability for the federally endangered Purshia subintegra (Kearney) Henrickson (Arizona cliffrose). We used deterministic matrix projection models and stochastic models simulating weather conditions during our study, given historical weather variation and under scenarios of increased aridity. Our models suggest that the P. subintegra population in Verde Valley is slowly declining and will be at greater risk of extinction with increased aridity. Across patches at a fine spatial scale, demographic performance was associated with environmental factors. Moist sites (patches with the highest soil moisture, lowest sand content, and most northern aspects) had the highest densities, highest seedling recruitment, and highest risk of extinction over the shortest time span. Extinction risk in moist sites was exacerbated by higher variance in recruitment and mortality. Dry sites had higher cumulative adult survival and lower extinction risk but negative growth rates. Steps necessary for the conservation of the species include introductions at more northern latitudes and in situ manipulations to enhance seedling recruitment and plant survival. We demonstrate that fine spatial‐scale modeling is necessary to predict where patches with highest extinction risk or potential refugia for rare species may occur. Because current climate projections for the 21st century imply range shifts at rates of 300 to 500 km/century, which are beyond even exceptional examples of shifts in the fossil record of 100–150 km, it is likely that preservation of many rare species will require human intervention and a long‐term commitment. Global warming conditions are likely to reduce the carrying capacity of many rare species' habitats.

Mating systems and limits to seed production in two Dicerandra mints endemic to Florida scrub - Margaret E.K. Evans; Eric S. Menges; Doria R. Gordon (Biodiversity and Conservation, 2004)

A Fire‐Explicit Population Viability Analysis of Hypericum cumulicola in Florida Rosemary Scrub - Pedro Francisco Quintana‐Ascencio; Eric S. Menges; Carl W. Weekley (Conservation Biology, 2003)
Land managers seeking to reestablish historical fire regimes need guidance on how to apply prescribed fire to promote the population persistence of endangered species. We explored extinction risks of Hypericum cumulicola , a fire‐dependent plant endemic to the Lake Wales Ridge, Florida ( U.S.A ). Stochastic and deterministic matrix population models based on six censuses ( 1994–1999 ) and data from several germination and seedling survival experiments were used to compare H. cumulicola demography and extinction probabilities under different fire regimes. Environmental variation associated with site, year, and winter precipitation was included in these models. We estimated time to extinction of unburned populations of different sizes and the probabilities of extinction under no fire, different regular fire‐return intervals, and alternating short and long fire‐return intervals. Following an initial fire, even relatively large populations of thousands of individuals may become locally extinct within 300–400 years without additional fires. Extinction probability declined as intervals between fires decreased. Fire intervals openface>50 years resulted in an appreciable extinction probability after 200 years. Cycles of highly staggered short and long fire‐return intervals caused slightly higher chances of extinction than regular fire‐return intervals. The simulations were sensitive to estimates of survival in the seed bank. Active management will be required to restore favorable fire regimes in areas where fire has been suppressed. To maintain biodiversity, managers should consider variable fire regimes to match the requirements of a variety of species with different life histories.

Population Viability: Evolving Tools for Declining Species - Eric Menges (Conservation Biology, 2003)

Emerging Issues in Population Viability Analysis - J. Michael Reed; L. Scott Mills; John B. Dunning; Eric S. Menges; Kevin S. McKelvey; Robert Frye; Steven R. Beissinger; Marie‐Charlotte Anstett; Philip Miller (Conservation Biology, 2002)
Population viability analysis ( PVA) has become a commonly used tool in endangered species management. There is no single process that constitutes PVA, but all approaches have in common an assessment of a population's risk of extinction (or quasi extinction) or its projected population growth either under current conditions or expected from proposed management. As model sophistication increases, and software programs that facilitate PVA without the need for modeling expertise become more available, there is greater potential for the misuse of models and increased confusion over interpreting their results. Consequently, we discuss the practical use and limitations of PVA in conservation planning, and we discuss some emerging issues of PVA. We review extant issues that have become prominent in PVA, including spatially explicit modeling, sensitivity analysis, incorporating genetics into PVA, PVA in plants, and PVA software packages, but our coverage of emerging issues is not comprehensive. We conclude that PVA is a powerful tool in conservation biology for comparing alternative research plans and relative extinction risks among species, but we suggest caution in its use: (1) because PVA is a model, its validity depends on the appropriateness of the model's structure and data quality; (2) results should be presented with appropriate assessment of confidence; (3) model construction and results should be subject to external review, and (4) model structure, input, and results should be treated as hypotheses to be tested. We also suggest (5) restricting the definition of PVA to development of a formal quantitative model, (6) focusing more research on determining how pervasive density‐dependence feedback is across species, and (7) not using PVA to determine minimum population size or (8) the specific probability of reaching extinction. The most appropriate use of PVA may be for comparing the relative effects of potential management actions on population growth or persistence.